THE INFLUENCE OF USING MIND MAPPING TECHNIQUE TO IMPROVE WRITING SKILL IN DESCRIPTIVE TEXT AT JUNIOR HIGH SCHOOL (META-ANALYSIS) - Nurani, Atika Ayu; Saputri, Tiyas (Konstruktivisme : Jurnal Pendidikan dan Pembelajaran, 2020)
This study is aimed to analyze the influence of mind mapping technique on learning outcomes of writing skills in descriptive text of Junior High Schoolstudents. The method used in this research was meta-analysis. The first step, researcher formulated the problem and then continue the collecting research data through google scholar search. From the search results, it is obtained 6 articles from journals and 4 relevant theses. The data obtained is reprocessed using quantitative methods. Based on the analysis results, Mind mapping technique is effective to improve learning outcomes in writing skills in descriptive text of Junior High Schoolstudents. Score of before and after learning using mind mapping technique presented significant difference score from the lowest 8.03% to the highest 67.68% with an average increase of 27.36%.